Breeding for postharvest physiological deterioration in cassava: problems and strategies - Wilton Mbinda; Asunta Mukami (CABI Agriculture and Bioscience)
Abstract Cassava is a major food crop for millions of people in Africa, Asia and South America, forming an essential food-security and income generation commodity for small-scale or subsistence farming communities. The storage root is the most important component of the crop that provides more calories than cereals. Immediately after harvest, cassava storage roots undergo complex biochemical and physiological changes known as postharvest physiological deterioration (PPD), which is influenced by genotype, environmental and agronomic factors, resulting to spoilage, rendering the storage roots unpalatable and unmarketable. This problem has remained unresolved over the years. This review describes the innovative breeding technologies which could be used to prolong cassava storage root shelf-life. In this review, we discuss the available knowledge on (i) physiology and biochemistry of cassava storage root with regard to PPD (ii) strategies for minimizing PPD in cassava storage roots (iii) traits associated with PPD tolerance as essential targets for prolonging cassava storage root shelf life, and (iv) suggestions for novel genomic tools and modern genetic and breeding approaches for prolonging shelf-life in cassava storage roots. With its extensive genomic resources including the public release of cassava reference genome sequence assembly and other and resources, and innovative plant breeding technologies, the crop offers an excellent opportunity to serve as a model to address postharvest spoilage and improve food security. Continuous improvements based on the new plant breeding technologies (genome editing, speeding breeding and RNA-dependent DNA methylation) in cassava and innovations in postharvest handling and storage of the storage roots are expected to provide sustainable solutions for PPD constraints and make cassava an important food security and nutrition and industrial crop.